Mechanics of Manipulation: A Comparative Analysis of Orwell’s 1984 and Chomsky’s Propaganda Model - Rahman, Afifa (Lembaga Sembilan Tiga Community, 2025)
1984 by George Orwell is a remarkable book which can be used to explain the symbiotic relationship between mass media and institutional structures. By using the propaganda model introduced and popularized by Edward S. Herman and Naom Chomskey, this paper intends to assess the components which are used to prompt a certain group of people to fall under a despotic influence where citizens, willingly, yet unwittingly, submit their agency to mass domination. In the process, this paper will investigate the agency of mass media in producing such willing but unwitting submissive citizens much like how